2005
DOI: 10.1080/02786820500352098
|View full text |Cite
|
Sign up to set email alerts
|

Method to Determine the Number of Bacterial Spores Within Aerosol Particles

Abstract: We describe methodology to reveal the number of microbial spores within aerosol particles. The procedure involves visualization under differential-interference-contrast microscopy enhanced by high-resolution photography and further analysis by computerassisted imaging. The method was used to analyze spore of Bacillus globigii in aerosols generated by a small (pressured metered-dose inhaler type) generator. Particles consisting in 1 or 2 spores accounted for 85% of all generated particles. This percentage rose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 12 publications
1
23
1
Order By: Relevance
“…This finding agrees with previous observations on the composition of aerosolized B. atrophaeus spores (Carrera et al 2005). Since bacteria in particles of different size could be differentially protected from UV inactivation, the data in Figure 4 indicates that all bacteria should be similarly exposed to UV without substantial protection by shielding inside clumps or large particles.…”
Section: Characterization Of Aerosol Exposuresupporting
confidence: 82%
“…This finding agrees with previous observations on the composition of aerosolized B. atrophaeus spores (Carrera et al 2005). Since bacteria in particles of different size could be differentially protected from UV inactivation, the data in Figure 4 indicates that all bacteria should be similarly exposed to UV without substantial protection by shielding inside clumps or large particles.…”
Section: Characterization Of Aerosol Exposuresupporting
confidence: 82%
“…This phenomenon is proposed to be due to larger particles containing higher numbers of bacteria in aggregates, enabling a fraction to survive deleterious stresses encountered during aerosolization. The outer layer of bacteria effectively is sacrificial, enabling the bacteria within the core of the aggregate to survive (4,28); such aggregation of B. atrophaeus spores was observed in this study (Fig. 3).…”
Section: Discussionmentioning
confidence: 67%
“…Carrera et al demonstrated that the output of the MDIs (0.05% [wt/wt]) used in this study could be particles containing single spores or particles containing multiple spores (7). In the first set of measurements, they used optical microscopy to determine particle area.…”
Section: Discussionmentioning
confidence: 99%